DFT Study: Geometry Optimization and Electronic Properties of Steroid Derivative Compounds - Ilham, Baso; Riskawati (Hayyan Journal, 2026)
This study presents a descriptive investigation of three steroidal compounds—6-hydroxystigmast-4-en-3-one (1), stigmast-4-en-3-one (2), and 3-hydroxystigmast-5-en-7-one (3)—using Density Functional Theory (DFT) at the B3LYP level with the 6-31G**(d,p) basis set. The calculations were performed to analyze the optimized geometries and electronic properties of the compounds. The presence of hydroxyl and carbonyl groups within these molecular structures revealed their roles as electron-donating sites and potential active centers for electrophilic attack. Furthermore, several quantum chemical descriptors, including chemical hardness (δ), softness (σ), electronegativity (χ), chemical potential (µ), and electrophilicity index (ω), were determined to provide insights into the reactivity and stability of the studied molecules.